(untitled) (Research, Society and Development, 2021)
Objective: To investigate the clinical profile and prescription of drugs used in the treatment of Covid-19 in patients admitted to the Unimed General Hospital in Belém, Pará, Amazon. Method: A cross-sectional, retrospective, exploratory, descriptive and analytical study on the use of medications applied to the treatment of Covid-19, with the period between April and October 2020 as a time frame. Results: It was observed that patients hospitalized with Covid-19, were predominantly diagnosed by the RT-PCR method, and most of them were aged ≥60 years, with one or more comorbidities. They presented leukocytosis, neutrophilia, lymphopenia, increased C-reactive protein and D-dimer CRP. The average hospital stay was 12 days. Elderly male patients showed greater vulnerability. The chance of death was very expressive in patients who required orotracheal intubation. A total of 3,398 potential interactions were found, revealing a higher absolute frequency of interactions of the pharmacodynamic type (n=2,233) compared to pharmacokinetic ones (n=1,165). Potential interactions were categorized, accounting for a total of 3,379; being (n=2.181) moderate, (n=734) severe and (n=464) mild. Conclusion: There was a proportional lower occurrence of deaths among patients who used dexamethasone compared to those who did not use it. There was a higher occurrence of deaths among users of enoxaparin and heparin compared to patients who did not use them. The medications oseltamivir, hydroxychloroquine and azithromycin also presented a risk association for the outcome of death.